Overvoltage Effects on Ground Grid Systems of Single and Two Neighboring High Voltage Substations - Krung Luewattana; Aphibal Pruksanubal (Institute of Advanced Engineering and Science, 2016)
The power networks with reliable transmission and distribution systems require high voltage substations with effective ground grid systems. Therefore, this study aimed to analyze the effects of overvoltage on ground grid systems within high voltage substations in two cases, including a single substation and the two neighboring substations, by using ATP/EMTP and ANSYS softwares. The simulations were performed to show both graphs and 3D results when the fault current flowed into the ground grids of substations at various positions. In case of the single high voltage substation, the overvoltage was highest when the fault current was injected at the corner of ground grid. However, in case of two neighboring high voltage substations, the levels of overvoltage were similar between that caused by injecting the fault current at the center and at the corner of ground grid. The simulation showed that overvoltage which occurring at the ground grid of high voltage substation A could permeate to the ground grid of nearby high voltage substation B, which nevertheless depending on the how the fault current was injected at different spots. The data from these simulations and analysis can be useful for future designs of ground grid systems with high reliability.